Three Critique of Edmund Husserl’s Theory of Intersubjectivity: Language, World and Culture - Balbontin-Gallo, Cristóbal (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The well-known theory of intersubjectivity, developed by Husserl in his Cartesian Meditations, has been the object of innumerable critique. The virtue of these critiques is that they are precisely those ones that have offered the possibility of renewing phenomenology as social theory. Our aim is to confront the Fifth Cartesian Meditation with other texts of the Husserlian corpus in order to propose three new critical entrances to his theory of intersubjectivity in relation to the question of language, the world and culture, and the insufficiencies that the Fifth Cartesian Meditation contains in the face of these presuppositions.
Keywords: intersubjectivity; other; social ontology; phenomenology; social philosophy